Partitions of Bengal - Neogy, Ajit K., 1937- (Calcutta : A. Mukherjee, 1987)
British administration in Bengal, 1905-1911.
Includes index.
Bibliography: p. [347]-352.
Keywords: Bengal (India) -- Politics and government